Relative Importance of Mineralogy and Organic Matter Characteristics on Macroaggregate and Colloid Dynamics in MG‐Silicate Dominated Soils. (18th May 2016) - Falsone, Gloria; Celi, Luisella; Stanchi, Silvia; Bonifacio, Eleonora
Abstract: Soil aggregation and organic matter (OM) conservation are important in the prevention of land degradation. Aggregation processes and OM turnover influence each other and depend on the characteristics of both minerals and organic pools. We assessed the relative importance of the organic and mineral phases at the macroaggregate and colloidal scale in two soils (CHL and SRP, chlorite and serpentine‐rich, respectively) where Mg‐silicates dominated, by incubating them with a relatively degraded and oxidized organic fraction, that is the humic acids (HAs) extracted from the organic horizons of both CHL and SRP. The HA from SRP were more aromatic and richer in phenolic groups, whereas HA from CHL were N‐richer, more aliphatic and richer in carboxyl groups. The SRP soil formed larger amounts of macroaggregates, more stable than in CHL. At the colloidal scale, SRP was more flocculated and clay had a lower electrophoretic mobility than CHL. HA enhanced aggregate formation in both samples but improved aggregate stability only in CHL. In CHL, slight differences in electrophoretic mobility were visible, while in SRP, differences were more pronounced, with a point of zero charge at lower pH and larger hydrodynamic diameter. The abundance of Mg in SRP may have favoured the formation of weaker outer‐sphere interactions and the release of clay‐HA associations upon water dispersion, while in CHL Ca formed more stable bonds with HA. In SRP, ligand exchange reactions can be ruled out, conversely to the dominant bonding mechanism occurring in Al‐silicate dominated soils, with important consequences on the release of OM‐loaded clay particles. Copyright © 2016 John Wiley & Sons, Ltd.